Agricultural policies against invasive species generate contrasting outcomes for climate change mitigation and biodiversity conservation - Pérez Méndez, Néstor (2022)
Fil: Pérez Méndez, Néstor. Institut de Recerca i Tecnologia Agroalimentàries. Sustainable Field Crops Program. España.